Effect of medial and lateral heel wedge changes On mechanical parameters of diabetic foot ulcers during gait - Ebrahim Abdi; Mansour Eslami; Mohand Taghipour (Islamic Azad University, Hamedan Branch, 2017)
Effect of medial and lateral heel wedge changes On mechanical parameters of diabetic foot ulcers during gait   Background: Still using the slope strategy on foot to reduce peak pressure and the pressure there is confusion. Therefore, the objective of this study was to evaluate the effect of internal and external wedge slope changes on the mechanical parameters foot ulcers. Methods: In this quasi-experimental study of 15 diabetic patients with an average age of 63.3±2.01 was used. The presence of 3, 6, 9 and 11 in both internal and external conditions we cover. Patients wearing the wedge in 9 separate efforts from the foot scan RS-scan data collection and analysis of variance for repeated data was prepared. Results: Compared with the control condition (bare feet), each lateral heel wedge significantly reduced peak pressure on 3, 4 and 5 metatarsal head (p=0.01), but, significantly increased peak pressure on 1 and 2 metatarsal head (p=0.01). Each medial heel wedge significantly reduced peak pressure on 1 and 2 metatarsal head (p=0.01), but, significantly increased peak pressure on 3, 4 and 5 metatarsal head (p=0.01) Time pressure integral showed a significant increase at the 3, 4 and 5 Metatarsal head area in the 3 lateral heel wedges, 9 and 11 degrees of medial heel wedges, And 1 and 2 metatarsal head regions was significant increase on the 9 and 11 degrees external and 11 degrees medial heel wedges (p=0.01). Conclusions: These findings indicate that heel wedges change effect was significantly different between the peak pressure and peak pressure time integral on the metatarsal head regions. A median slope of 6 degrees can also be suitable for reducing the peak pressure in the three, four, and five metatarsal head, as well as a 6 degree can also be suitable for reducing the peak pressure in the metatarsal head.